The frequencies of localized acoustic modes in Au/V nanolayers with capping layer - Aleksiejuk, M. (Archives of Acoustics, 2006)
Paper presents the results of theoretical analysis of localized acoustic modes, which can be generated in Au/V nanolayers with “heavy” capping layer. The transfer-matrix method was used to evaluate frequencies of localized acoustic modes in these nanostructures. Up to now the condition of generation of localized modes in nanolayer structure was that the acoustic impedance of capping layer is lower then the acoustic impedance of top (next) layer. This condition was in agreement with experimental results. This paper demonstrates the possibility of generation of localized acoustic modes in case of higher acoustic impedance of capping layer. The frequencies of localized modes for different thickness of capping layer were obtained.